HUMAN IMMUNODEFICIENCY VIRUS PADA KOMUNITAS GAY DI KAWASAN MARINA PLAZA KOTA MANADO - Jasman Jasman; Dismo Katiandaghob; Moningka Dely Natalia; Ronny Muntud (POLTEKKES KEMENKES MANADO, 2019)
Human Immunodeficiency Virus (HIV) is a virus that causes Aquired Immunodeficiency Syndrome (AIDS) by attacking white blood cells, namely CD4 cells (Cluster of Differentiation 4) that can damage the human immune system. Without the immune system, a person is easily attacked by various diseases. The number of HIV / AIDS sufferers according to data from the Tikala Baru Health Center VCT in 2018 totaled 62 people. The aim of this study is to identify HIV in the Gay Community in the Marina Plaza Area of ​​Manado City. The method used in this study is the Immunocromatography Test using One Step Anti-HIV. Sampling was carried out in the Marina Plaza Area and immediately examined at the sampling location. The population in this study is the entire Gay Community in the Marina Plaza Area of ​​Manado City with a total population sampling method. This type of research is descriptive, research results are presented in tabular form and narrated.Based on research conducted, it can be concluded that, of the 85 respondents examined there were 1 positive respondent and 84 negative respondents. It is recommended for members of the gay community who are infected with HIV to take ARV (Anti Retroviral) drugs regularly. For gay community members who have not been infected with HIV in order to prevent transmission by using a condom during sex or leaving deviant sexual behavior.